Total Quality Management Practices on Firm Performance: A Study of Selected Deposit Money Banks in Nigeria - Ejikeme Emmanuel Isichei; Samuel Taiwo Olabosinde (Romanian Economic Journal, 2025)
This study investigates the impact of Total Quality Management (TQM) on the efficiency and effectiveness of Nigerian deposit money institutions, with a particular focus on enhancing financial performance and customer satisfaction through quality initiatives. Drawing from a comprehensive review of theoretical and empirical literature, the research offers a nuanced understanding of the critical role of TQM in the banking sector. Employing a survey research design, data were collected from a sample of 122 respondents using a Likert scale questionnaire. The reliability of the survey instrument was assessed through the split-half method, yielding a reliability index between 0.85 and 0.91, and content validity was established through expert review. Data analysis was conducted using SPSS, applying descriptive statistics and multiple regression techniques to assess the relationship between TQM practices and organizational performance. The findings reveal that TQM significantly enhances both operational efficiency and customer satisfaction. However, the study underscores that mere awareness of TQM principles is insufficient for organizational excellence; effective implementation is key. The study concludes that TQM is a vital strategy for achieving customer satisfaction and recommends rigorous monitoring of TQM implementation and strengthening internal control systems to mitigate quality-related costs and curb fraud within the industry. These insights provide valuable implications for policymakers and practitioners aiming to bolster the competitiveness of financial institutions through quality management practices.